Leibniz algebras, having a dense family of ideals - Semko, N.N.; Skaskiv, L.V.; Yarovaya, O.A. (Carpathian Mathematical Publications, 2020)
We say that a Leibniz algebra $L$ has a dense family of ideals, if for every pair of subalgebras $A$, $B$ of $L$ such that $A\leqslant B$ and $A$ is not maximal in $B$ there exists an ideal $S$ such that $A\leqslant S\leqslant B$. We study the Leibniz algebras, having a dense family of ideals.